The Future of Gender Policies in the Globalized World: Russian Case - Liudmila Aleksandrovna Vasilenko; Marina Aleksandrovna Kashina (Управленческое консультирование)
The nonlinearity of social development presupposes a plurality of meanings and paths of the future. For good governance is necessary to determine the full range of factors that can cause change in the direction of flow of social processes. One of these factors in a globalized society becomes the character of relationships between women and men. In world practice there are four different approaches to gender issues. The first two can be defined as traditional , the latter two as innovative. Their innovativeness is related to the revision of attitudes towards gender as invariable and biological. Gender competence of the officials becomes a guarantee of real and effective administrative impact on gender relations. Only in this case the human potential of men and women can be used for the development of society. The modern Russian gender policies can be described as a return to the past. There is a return to the patriarchal family values, actualization of the traditional roles of women and men in the public mind, the use of traditional administrative methods of solving the gender issues. The factors that determined this state of affairs can be combined into four groups: underestimation of the social component of economic development, the desire to dissociate itself from the western (European) values as irrelevant to the Russian mentality, the absence in the public mind a clear idea of gender equality, a change of generations in the Russian gender studies and women’s movement.